Temperature and Temperature Stress Design in the Sides of Moving Melts Passages - R. I. Esman (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The analysis of heat and thermo-stressed state of plane channels with moving melts of liquid metals is carried out.The developed mathematical model and numerical experiment allow to determine the main control parameters of special types of casting for fabricating thin pieces by pressing, liquid stamping methods and low pressure die and regulated casting.